Prevalence of paucibacillary cases of leprosy in Brazil: a 20-year systematic review and meta-analysis - Brito Gonçalves, Bruna Eduarda; Raiol, André Matheus Porto; Brito, Ana Vitória Cruz; Silva, Marcos Jessé Abrahão; Sardinha, Daniele Melo; Lima, Karla Valéria Batista; Lima, Luana Nepomuceno Gondim Costa (Frontiers in Medicine, 2024)
Introduction Leprosy is a chronic infectious disease caused by the agent Mycobacterium leprae, characterized by its high disabling power. Data points to Brazil being the second country with the highest number of cases in the world, behind only India, representing a major challenge for public health. This work aims to determine the prevalence of paucibacillary (PB) cases in relation to leprosy cases in Brazil, using data published in the literature. Methods This is a systematic review and meta-analysis carried out with studies from the last 20 years, being developed based on the Preferred Reporting Items for Systematic Review and Meta-analyzes (PRISMA).The search was carried out in the databases: PUBMED, SciELO, LILACS (via VHL)and Science Direct in October 2023, using the following descriptors (((“Brazil” [Mesh]) AND (“Leprosy, paucibacillary” [Mesh])) AND “Epidemiology” [Mesh]), in English, Portuguese and Spanish. Original studies of the analytical case–control, cohort, cross-sectional, epidemiological types were selected, as well as articles with satisfactory information for numerical extraction with separate data on the paucibacillary and multibacillary clinical forms. The methodological quality assessment followed the JBI critical appraisal checklist. Statistical analysis was performed using the Comprehensive Meta-Analyses-CMA software, version 3.0 (Biostat, Engewood, NJ, United States). Results The meta-analysis of the 48 studies obtained a paucibacillary prevalence rate in Brazil of 50.5% or 0.505 (95% CI = 0.502–0.509).The differences in the analyzes were statistically significant (Q-value 4302.681;df 47; I 98.905), with a high heterogeneity value evidenced by I2 (98.905). This analysis demonstrated that the frequency in the Midwest region was the highest and the South region was the lowest (21.4%). Begg’s (Kendall Tau p = 0.35) and Egger’s tests (p = 0.20) were performed, in which no high publication bias was noted. Subgroup analysis indicated that paucibacillary cases varied from region to region, with the Midwest region having the highest prevalence and the South region having the lowest. Conclusion The results stand out significantly for the research gaps that investigate PB cases, requiring more research aimed at investigating the paucibacillary clinical form that can contribute to the early diagnosis of leprosy. Systematic review registration PROSPERO code: CRD42024514106.